Crustal thickness and lithospheric properties of Mercury constrained by gravity data - Qingyun Deng; Mao Ye; Weifeng Hao; Chi Xiao; Zhen Zhong; Denggao Qiu; Wensong Zhang; Chong Zheng; Yichen Wang; Jianguo Yan; Jean-Pierre Barriot; Zhiyong Xiao; et al. (Geo-spatial Information Science)
The crust and lithosphere of Mercury record the footprints of exogenous and endogenous activities since its formation, and their physical properties provide important clues for understanding the overall evolution of Mercury. The gravity field contains information about the internal structure of this innermost planet. Although the Mercury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) mission acquired the best-quality orbital tracking data for Mercury, the solved gravity field models still suffer from the uneven resolution between the northern and southern hemispheres, in which broad gravity anomalies in the northern mid-latitude region and small-scale anomaly features in the high-latitude region are revealed. With gravity and topography data, the crustal thickness and lithospheric elastic thickness are inferred through geophysical modeling. The average crust thickness is estimated to be either 35 [Formula: see text] 18 or 26 [Formula: see text] 11 km based on different topography compensation models, indicating intensive crustal production during the early evolution epoch. The global crustal thickness variations are obtained by inverting the Bouguer gravity anomaly, which is suggested to be correlated with the mantle uplift of large impact basins, partial melt of mantle materials, or/and intra-lithosphere contractional strain. The temperature structure of the lithosphere indicated from the elastic thickness (Te) with strength model are correlated to internal thermal evolution. The ongoing Bepi-Colombo mission is expected to improve the Mercury gravity field model, which will greatly enhance the application of these geophysical models to Mercury. The scientific results related to Mercury’s crust and lithosphere provide a reference for studies of the Moon, Mars, and Callisto.